Performance analysis of conventional multilevel inverter driven PMSM drive in EV applications - Shriwastava, Rakesh G.; Pokle, Pravin B.; Mendhe, Ajay M.; Dhote, Nitin; Rewatkar, Rajendra M.; Mapari, Rahul; Dhunde, Ranjit; Patil, Hemant R. Bhagat; Pawase, Ramesh (International Journal of Applied Power Engineering (IJAPE), 2025)
This paper describes the simulation and hardware analysis of a two-level inverter-driven permanent magnet synchronous motor (PMSM) drive in EV applications. The design of various sections of PMSM Drive is discussed in detail. This proposed work is based on the voltage source converter (VSC) fed four-pole, 373 W. This paper highlights the design and implementation using a microcontroller of (PMSM) drive for various operating conditions. The experimental results show that the control and power circuit used in the design can achieve excellent and consistent speed performance. The performance along with test results of the speed and load variation of the PMSM drive is studied for steady-state conditions. The performance of the motor has been checked by increasing the inverter frequency with the speed of the motor and also keeping the frequency remains constant by varying the load and speed. Hardware analysis indicates the improved performance of the motor and the drive. It has good speed and torque responses and is suitable for EPS applications.